Efficacy of peroxyacetic acid against Salmonella biofilms and as a decontaminant agent in poultry meat - Onaran Acar, Bahar; Cengiz, Gorkem; Gulendag, Erman; Goncuoglu, Muammer; Diker, K. Serdar (Journal of the Hellenic Veterinary Medical Society, 2022)
We aimed to investigate the effect of the post-chilling Peroxyacetic Acid (PAA) application on chicken carcasses’ shelf life, PAA treatment on chicken neck skin samples contaminated with S. Enteritidis and S. Typhimurium serotypes, and its activity against single and mixed Salmonella biofilms. Initially, effects of the post-chilling PAA application on chicken carcasses’ shelf life was analyzed. Secondly, the effectiveness of PAA application in chicken neck skin samples which are experimentally contaminated was investigated. Then, biofilm forming capacity of Salmonella enterica serovars were determined, and PAA activity against single and mixed Salmonella biofilms was evaluated. According to the results, in all experimental groups at least 1 log cfu/g reduction was observed on the day of PAA application (0 hour), and we monitored significant decreases of Salmonella counts in all groups after both 100 and 200 ppm PAA treatments within the 6th hour. The combinations of PAA concentrations and duration of application used in the study were insufficient in terms of S. Typhimurium and S. Enteritidis counts in chicken neck skin samples; however, these treatments can be effective on extending the chicken meat’s shelf life. On the other hand, 200 ppm of PAA was effective in reducing S. Typhimurium and S. Enteritidis biofilms. As a mean of 4.8 log/ml reduction were detected against S. Enteritidis and S. Typhimurium biofilms. Moreover, we can conclude from statistical analysis that when biofilm is composed with more than one Salmonella, it is harder to reduce their counts with PAA treatments. However, there is a recommendation of EFSA (European Food Safety Authority) that PAA may be a decontamination agent in poultry production in the future, considering that PAA will not have toxic effects on human health. PAA studies on this subject will be of great importance in the future if it is passed to legislation.